Packaging Design and Digital Marketing Management in Educational Culinary Ventures: Their Influence on Purchase Decisions Mediated by Brand Image - Nadia Sri Rezeki; Fithriawan Nugroho (Al-Qalam Institue, 2026)
This study aims to analyze the influence of packaging design and digital marketing management on purchase decisions in educational culinary ventures, with brand image serving as a mediating variable. The research is grounded in an educational management perspective, particularly in understanding how the managerial implementation of marketing-related competencies within educational-based culinary enterprises contributes to consumer decision-making. A quantitative approach with a causal associative design was employed. Data were collected from 140 consumers of culinary products produced by educational culinary ventures in Pangkalpinang using structured questionnaires. The data were analyzed using Structural Equation Modeling with the Partial Least Squares approach (SEM-PLS) through SmartPLS 4. The results indicate that packaging design and digital marketing management have significant positive effects on brand image. Furthermore, digital marketing management and brand image significantly influence purchase decisions. Packaging design does not exert a significant direct effect on purchase decisions; however, its effect becomes significant when mediated by brand image. Brand image emerges as the most dominant factor influencing purchase decisions. The structural model explains 57.1 percent of the variance in brand image and 59.3 percent of the variance in purchase decisions, demonstrating strong predictive power. These findings imply that effective educational management of culinary ventures should emphasize the integration of packaging design and digital marketing within entrepreneurship learning programs, as brand image plays a critical role in translating educational-based marketing practices into sustainable consumer purchasing behavior.